2023
DOI: 10.1021/acsabm.3c00277
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise Targeting and Antibacterial Strategy by Leukocyte Membrane-Based Conjugated Oligomer Nanoparticles

Abstract: Bacterial infection poses an enormous threat to human life and health. The inability of drugs to be effectively delivered to the site of infection and the development of bacterial resistance make the treatment process more difficult. Herein, a stepwise targeted biomimetic nanoparticle (NPs@M-P) with inflammatory tendency and Gram-negative bacterial targeting was designed, which can achieve efficient antibacterial activity under near-infrared triggering. Leukocyte membranes and targeted molecules (PMB) are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…32,33 To endow it with advances of the NIR responsive property, we fabricate a hydrogel composite based on PIC and ETTC conjugated polymer nanoparticles. As illustrated in Scheme 1a, ETTC NPs were prepared by nanoprecipitation together with amphiphilic polymer (DSPE-PEG-2000) 34 and exhibit a broad NIR absorption spectrum with a prominent shoulder at 808 nm (Figure S1). Whereafter, NPs were encapsulated within cell membrane extracted from extracted from skin fibroblast L929 cells to form the camouflaged CM@ NPs using ultrasound.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 To endow it with advances of the NIR responsive property, we fabricate a hydrogel composite based on PIC and ETTC conjugated polymer nanoparticles. As illustrated in Scheme 1a, ETTC NPs were prepared by nanoprecipitation together with amphiphilic polymer (DSPE-PEG-2000) 34 and exhibit a broad NIR absorption spectrum with a prominent shoulder at 808 nm (Figure S1). Whereafter, NPs were encapsulated within cell membrane extracted from extracted from skin fibroblast L929 cells to form the camouflaged CM@ NPs using ultrasound.…”
mentioning
confidence: 99%
“…Because of these highly biomimetic characteristics, previous studies have demonstrated that PIC hydrogels can respond to cell tractions to form bidirectional cell–matrix interactions and facilitate connective tissue regeneration in an abdominal wound model and stay adherent to the wound without additional support. , To endow it with advances of the NIR responsive property, we fabricate a hydrogel composite based on PIC and ETTC conjugated polymer nanoparticles. As illustrated in Scheme a, ETTC NPs were prepared by nanoprecipitation together with amphiphilic polymer (DSPE-PEG-2000) and exhibit a broad NIR absorption spectrum with a prominent shoulder at 808 nm (Figure S1). Whereafter, NPs were encapsulated within cell membrane extracted from extracted from skin fibroblast L929 cells to form the camouflaged CM@NPs using ultrasound .…”
mentioning
confidence: 99%